KESADARAN BERAGAMA MASYARAKAT JAMBI KOTA SEBERANG - Hendra Gunawan (Prodi Sosiologi Agama, 2020)
This field research is about the religious awareness of the community in Kelurahan Olak Kemang and Kelurahan Ulu Gedong. With the analytical descriptive method, this research attempts to describe the data as it is obtained from the field. From the data analysis, it is known that the level of religious awareness in the community in Olak Kemang and Ulu Gedong villages is quite high. This can be seen in the pattern of their lives that highly uphold Islamic religious values as has been done by previous scholars. The high level of religious awareness in the community of Olak Kemang and Ulu Gedong villages is inseparable from the role of ulama, and two social institutions in the form of madrasah and places of worship. Even though the level of religious awareness in the community is quite high, one must be aware of the idea of reform in religion in Jambi Seberang, which has suffered damage due to errors regarding different interpretations.